The chemical interaction of support and active phase in sintering resistant La0.8Ca0.2FeO3 perovskite catalysts. (1st May 2019) - Jing, Zhongyu; Li, Huaiyou; Jiang, Zhidong
Graphical abstract: Highlights: La0.8 Ca0.2 FeO3 perovskite (LCF)/n-MgAl2 O4 spinel (MgAl), molar ratio n = 2.5 or 4, by deposition-precipitation. The catalyst activity, sintering resistance and chemical stability of LCF/nMgAl are greatly improved over LCF. MgAl promotes LCF via chemical modification of the active structure rather than physical segregation. Abstract: The activity and sintering resistance of La0.8 Ca0.2 FeO3 perovskite (LCF) were found both improved in catalytic combustion of methane once dispersed on MgAl2 O4 spinel (MgAl) support, which may attribute to the interaction of LCF and MgAl. To probe the mechanism, the LCF/nMgAl composite catalysts (n = 2.5 or 4, molar ratio of MgAl/LCF) were prepared by deposition-precipitation method and characterized. The results showed that on surface of bulk LCF, lattice FeL 3+ dominated; yet after TPR/Re-oxidation treatments, a substantial portion of lattice FeL 3+ transformed to free FeF 3+, accompanied by a drastic drop in activity. While on LCF/nMgAl surface, the ratio of FeF 3+ /FeL 3+ increased with n; and substitution of Ca 2+ by Mg 2+ occurred, even up to 100% in LCF/4MgAl. As the result, LCF/4MgAl demonstrated a nearly doubled activity and much improved stability against 1000 °C calcination with respect to bulk LCF. The thinner coverage of LCF on MgAl in LCF/4MgAl has enhanced the interaction, which resulted a smaller Ea value as 100.6 kJ·mol −1, in contrast to 123.1 kJ·mol −1 and 134 kJ·mol −1 for LCF/2.5MgAl and bulk LCF, respectively. More importantly, after subjecting to three round redox treatment, surface species of the LCF/nMgAl catalysts changed little and the activity and Ea even upraised slightly. Therefore, compositing with MgAl has modified the structure of active centers of LCF on chemical aspects, rather than by physical segregation or textual promotion, which is the main reason that improves the catalytic activity, stability and sintering resistance of LCF.